Inovasi dan Kreativitas Usaha Keripik Singkong Ibu Imah Rosyidah di Masa Pandemi Covid-19 - Nani Nani; Reni Hindriari; Agus Sulaeman Anhari (Indonesian Journal of Society Engagement, 2022)
Since the outbreak of the corona virus (Covid-19) pandemic that occurred both domestically and abroad, almost all snack food business sectors have experienced a slump. One of the businesses that is still able to survive the pandemic is the cassava chips business. Because the cassava chip business is growing day by day, it is increasingly able to adapt to the development of current tastes and trends. The flavors given by the typical cassava chips include savory and crunchy. The cassava chip business is included in the micro, small and medium enterprises during the pandemic and is currently experiencing a very significant decline. In this case, business actors operating on a medium-low scale, namely the cassava chips business run by Mrs. Imah, having her address at Pengsinan Gunung Sindur Village, Bogor, have experienced a 50% decrease in sales from the previous one. For this reason, in order to keep attracting consumers, creativity and innovation are needed in developing cassava chips business products. Community service carried out by Pamulang University Lecturers has the aim of providing assistance and assistance to micro, small and medium business actors how to create innovation and creativity from the cassava chip product. The method used in this community service is by way of observation, namely observing and direct surveys to the field. From the results of the survey, it can be concluded that this business is not supported by local government agencies, especially the cooperatives and banking services, because the capital factor is also very important for the sustainability of the business going forward. In addition, innovation and creativity factors also need to be improved continuously so that they are not abandoned by consumers. Some of these obstacles need to be given attention because they have an important role for the development of the snack food industry.